Influence of Gestation Delay and Predator's Interference in Predator-Prey Interaction under Stochastic Environment. (7th April 2014) - Jana, Debaldev
Abstract : Previous experimental and theoretical studies suggest that predator's interference in predator-prey relationship provides better descriptions of predator's feeding over a range of predator-prey abundances. Also biological delays and environmental stochasticity play an important role to describe the system and its values. In this present study, I consider a Gaussian white-noise induced stochastic predator-prey model with the Beddington-DeAngelis functional response and gestation delay. Stochastic stability is measured by second order moment terms by calculating the nonequilibrium fluctuation of the nondelayed system and Fourier transform technique depicts the fluctuation of stochastic stability by introducing time lag. Different dynamical behaviors for both situations have been illustrated numerically also. The biological implications of my analytical and numerical findings are discussed critically.